Interações funcionais de uma semeadora-adubadora: aplicação estratégica e precisa de sementes graúdas e insumos alinhada aos princípios da agricultura digital - Santos, Bruna Karine dos (2024)
In the national context, agricultural commodities play a fundamental role in the production of animal protein, human food, and alternative energy sources. In Brazil, there is still potential to expand cultivable areas for agriculture. However, in many other countries, geographic expansion of arable land is limited, making it indispensable to increase crop yields. This yield increase can be achieved through modern machinery, equipment, and techniques. In this context, this research focuses on precision planters for large seeds, as the successful establishment of seeds in the soil contributes to the success of the future harvest. For the development of innovative products, investment in research and development is essential. This thesis aims to present a functional structure model for a planter-fertilizer for large seeds, enabling the strategic and precise application of seeds, fertilizers, and inoculants aligned with the principles of digital agriculture. The methodology used in this research was structured in six steps: (i) The focus theory involved research in books, articles, dissertations, theses, and technical materials from agricultural machinery manufacturers. This information was related to the Influencing Factors in Design through their classification into classes and properties; (ii) Analysis of the technical-operational process considered the focus theory and field visits to define the initial and final states of the processed elements; (iii) Definition of the global function was based on the objective of the planter-fertilizer machine; (iv) Rewriting the technicaloperational process in terms of functions, using terms composed of verbs and nouns, allowed for identifying the main flow of the functional structure; (v) Breaking down the global function into partial and elementary functions, including interactions of energy, material, and signals; (vi) Evaluation of the developed functional structure involved a comparative analysis of the functions found in commercial machines available in the Brazilian market. The definition of the global function resulted in identifying 42 partial functions and 122 elementary functions, as well as the interactions of energy, material, and signal flows. The evaluation of the developed structure, compared to machines available in the Brazilian market, indicates that the functional structure of the planter-fertilizer achieved its purpose of explicitly defining the global function. It also revealed that the proposed structure is more comprehensive than the evaluated commercial machines. Thus, it is concluded that there is still room for innovation and improvement in the development of planter-fertilizer machines. Future technologies for these machines should include systems that dynamically adjust to field conditions, ensure the precise and strategic application of inputs, and provide real-time data, facilitating more assertive decision-making.